2014
DOI: 10.1007/s00277-014-2155-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of anemia and its impact on the state of frailty in elderly people living in the community: SADEM study

Abstract: Anemia represents a global health problem that negatively impacts quality of life in elderly population; however, its impact on the geriatric syndrome of frailty is unclear. We examined the prevalence of anemia among elderly and sought a relationship between hemoglobin and the phenotype of frailty. Baseline hemoglobin quintiles and anemia were assessed in relation to frailty status in a prospective study with 1,933 older community-dwelling adults enrolled in the Study on Aging and Dementia in Mexico (SADEM). L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 28 publications
2
32
0
1
Order By: Relevance
“…56 Using this definition, not unexpectedly in patients undergoing CTX, all three classes of older patients were anemic. This problem is important to evaluate in older adults because anemia is associated with decreased physical performance, 57 an increase in the number of falls, 58 frailty, 57,59,60 increase in depressive symptoms, 61,62 increase in the number of hospitalizations, 63 and increased mortality. 64,65 While the level of anemia observed in this study may not warrant routine treatment in oncology patients, clinicians need to monitor older adults receiving CTX more carefully to evaluate the impact of anemia on their ability to function.…”
Section: Discussionmentioning
confidence: 99%
“…56 Using this definition, not unexpectedly in patients undergoing CTX, all three classes of older patients were anemic. This problem is important to evaluate in older adults because anemia is associated with decreased physical performance, 57 an increase in the number of falls, 58 frailty, 57,59,60 increase in depressive symptoms, 61,62 increase in the number of hospitalizations, 63 and increased mortality. 64,65 While the level of anemia observed in this study may not warrant routine treatment in oncology patients, clinicians need to monitor older adults receiving CTX more carefully to evaluate the impact of anemia on their ability to function.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] A specific cause cannot be found in approximately 37% to 45% of cases of anemia in the elderly, despite investigations in search of an etiology. [5][6][7] The terms "anemia of unknown etiology" (AUE) and "unexplained anemia in the elderly" are used to describe this population of patients with unexplained or senile anemia.…”
Section: Introductionmentioning
confidence: 99%
“…Frailty was significantly associated with the use of vitamin D (r = 0.16; p = 0.03), hemoglobin (r = ‐0.14; p = ‐ 0.02) and intact parathyroid hormone (r = 0.16; p = 0.03) . Anemia was associated with frailty in both cross‐sectional and longitudinal analyses, and anemia precedes frailty in men who were nonfrail at baseline, which indicated that anemia was independently associated with an increased risk of frailty . This may be explained by the hypothesis that anemia produces fatigue and reduces muscular oxygenation, which can affect muscular strength and quality and, later, physical performance …”
Section: Risk Factors Of Ckd and Biological Mechanisms Of Ckd‐inducedmentioning
confidence: 96%
“…74 Anemia was associated with frailty in both cross-sectional and longitudinal analyses, and anemia precedes frailty in men who were nonfrail at baseline, which indicated that anemia was independently associated with an increased risk of frailty. 75,76 This may be explained by the hypothesis that anemia produces fatigue and reduces muscular oxygenation, which can affect muscular strength and quality and, later, physical performance. 77 Sleep disordered breathing (SDB) is common among chronic kidney disease (CKD) patients and is a risk factor for cognitive dysfunction in the general population.…”
Section: Nontraditional Vascular Factorsmentioning
confidence: 99%